THE SOCIO-ECONOMIC OF OIL PALM FARMERS IN THE ABANDONED SHRIMP AREA KHANABNAK SUB-DISTRICT PAKPHANANG DISTRICT NAKHON SI THAMMARAT PROVINCE - เนื่องมัจฉา, ปิยวรรณ; เหมทานนท์, สุพพัต (Academic Journal Phranakhon Rajabhat University, 2019)
The purpose of this research was to study the socio-economic of oil palm farmers in the abandoned shrimp area Khanabnak sub-district Pakphanang district Nakhon si Thammarat province since it was area which has rapidly changed land use from abandoned shrimp farms to oil palm. The sample was 112 households of oil palm farmers in 10 villages of Khanabnak sub-district Pakphanang district Nakhon si Thammarat by using questionnaires and interviews. The results was found that 50.89 percent of farmers were male, 57.14 percent of farmers had average age between 46 - 55 years, 32.14 percent of farmers were elementary school, 39.29 percent of land use before oil palm planting was shrimp farm, and 67.86 percent of farmers had experience in oil palm plantations for 6 - 10 years. For the economy, total area of holding was 11 - 20 rai per household, 35.71 percent. The area of ​​oil palm plantations was less than 10 rai per household, 37.50 percent. Expenses in oil palm plantations was higher than 240,001 baht per year, 31.25 percent. Income from oil palm plantations was higher than 500,001 baht per year, 31.25 percent. Most of the farmer’s savings was higher than 100,000 baht per year, 63.39 percent. Production factors found that 22.32 percent of oil palm in Khanabnak sub-district was Univanich oil palm, 37.50 percent of oil palm was harvested at the age of 3 years, and most farmers use chemical fertilizer formula 15:15:15 (N: P: K) at the rate of 20 kg per rai. In addition, the worth of the investment of oil palm plantation in Khanabnak sub-district was found that oil palm cultivation was possible in making investment decisions. Since the oil palm plantation had a positive benefit-to-cost ratio (BCR), the internal rate of return for oil palm plantation (IRR) was higher than the opportunity cost of capital (Loan interest rate of commercial banks) which shows that it was worth the investment. And when considering the net present value (NPV) found that the value was positive. It was shown that oil palm cultivation was profitable and can make investment decisions.